Analysis of different drug extraction methods in biological fluid samples for LC-MS/MS assays: scoping review - Sandrin, Viviane da Silva Siqueira (2022)
The purpose of this study was to carry out a systematic investigation and analysis of different drug extraction methods, specifically non-steroidal anti-inflammatory drugs in biological fluid samples, for Liquid Chromatography in Mass Spectrometry assays. The search was carried out in PubMed, Scopus (Elsevier), Scientific Electronic Library Online (SciELO), Google Scholar, and the Digital Library of Theses and Dissertations of the University of São Paulo, between 1999 and 2021, following the guidelines of the Preferred Reporting guide. Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRSMA-ScR) Checklist. The search strategy was carried out with Boolean operators (AND and OR), where initially 248 articles were selected. After verification by two independent reviewers, removal of duplicates, reading of titles, abstracts, and full text, 39 publications that met the inclusion and exclusion criteria (previously established) were obtained. In 52% of the studies, the authors used the liquid-liquid extraction method, while in 41% the solid-phase extraction method was used. 5% used microextraction methods and 2% used less conventional techniques. Liquid-liquid extraction is the technique commonly used in sample preparation and the one with the highest selectivity, compared to simple solvent extraction methods, and the oldest of the techniques applied to determine chemical compounds. However, even though it has wide use and good analytical performance, liquid-liquid extraction has several disadvantages, such as the need for large volumes of samples and organic solvents. Currently, liquid-liquid extraction is considered an expensive, time-consuming technique and does not meet the current requirements of green analytical chemistry, that is, going against innovative trends in sample handling and faster, safer, and more environmentally friendly extraction techniques.